On the suitability of the Thorpe–Mason model for calculating sublimation of saltating snow - Sharma, Varun; Comola, Francesco; Lehning, Michael (The Cryosphere, 2018)
The Thorpe and Mason (TM) model for calculating the mass lost from a sublimating snow grain is the basis of all existing small- and large-scale estimates of drifting snow sublimation and the associated snow mass balance of polar and alpine regions. We revisit this model to test its validity for calculating sublimation from saltating snow grains. It is shown that numerical solutions of the unsteady mass and heat balance equations of an individual snow grain reconcile well with the steady-state solution of the TM model, albeit after a transient regime. Using large-eddy simulations (LESs), it is found that the residence time of a typical saltating particle is shorter than the period of the transient regime, implying that using the steady-state solution might be erroneous. For scenarios with equal initial air and particle temperatures of 263.15 K, these errors range from 26 % for low-wind, low-saturation-rate conditions to 38 % for high-wind, high-saturation-rate conditions. With a small temperature difference of 1 K between the air and the snow particles, the errors due to the TM model are already as high as 100 % with errors increasing for larger temperature differences.